Think pair share cooperative learning model and critical thinking skills students at xaverius 1 junior high school in Bandar Lampung - Widya Lestari; Burmansah Burmansah; Taridi Taridi (Universitas Sebelas Maret, 2025)
The ever-changing dynamics of the world of education demand that students improve various competencies in order to face the challenges of the 21st century. One of the most important competencies to develop is critical thinking skills. These skills enable students to analyse information, evaluate arguments, and make logical and rational decisions. To develop this ability, it is necessary to apply an appropriate learning model, one of which is the Think Pair Share (TPS) learning model. The TPS model is designed to encourage active student participation through independent thinking, discussion with partners, and sharing the results of discussions in large groups. This study aims to determine the effect of the TPS learning model on students' critical thinking skills at Xaverius 1 Junior High School in Bandar Lampung and the extent of this effect. This study used a survey method with a quantitative approach. Data collection techniques were carried out by distributing questionnaires using a Likert scale. The research population consisted of 38 students, and the entire population was used as the sample (saturated sampling). Data analysis was performed using simple linear regression tests with the help of SPSS version 27 software. The results of the analysis showed a positive and significant effect between the application of the TPS model and students' critical thinking skills, with a contribution of 62.6%. These findings indicate that the more optimal the application of the TPS model in the learning process, the higher the critical thinking skills possessed by students. Based on these results, the TPS learning model is recommended as an effective and relevant learning strategy to be applied in order to improve students' critical thinking skills at the junior high school level.